The Moose Trappers and Hunting Grounds of Vilhelmina - Lars Göran Spång; Wiebke Neumann; David Loeffler; Göran Ericsson (Current Swedish Archaeology)
Archaeological research in northern Sweden has customarily proposed models based on assumed migration patterns to portray resource utilization of prehistoric hunter-gatherers. An average hunting household needs about 500km2 for its subsistence. This assumption, as well as the temporal and spatial distribution of animal resources available for hunting households in the interior of Northern Sweden, is investigated using Agent Based Modelling (ABM) with explicitly identified factors and conditions. ABM simulations were run in order to analyse the relationships between hunters, moose (Alces alces), predators, landscapes and how human migration patterns could be adjusted in order to coincide with moose migrations. The results suggest that wolves and human hunters could coexist if the landscape had a moose density of 0.6 moose/km2 or more and if each hunting household possessed territories of 400–500km2. In accordance with the model’s parameters, the simulation identifies those factors that are particularly sensitive to change and those factors that are necessary in order to maintain an ecological balance between hunters and their prey.